Functional Eloquence Weighted Imaging: A Novel Modality to Select Patients With Large Vessel Occlusion Stroke. (16th November 2021) - Sajja, Kalyan Chekravarthy; Male, Shailesh
Abstract : 2015 was a great year for acute stroke care as the results of 5 randomized controlled trials revealed overwhelming benefit of mechanical thrombectomy (MT) for large vessel occlusion (LVO) ischemic strokes. The HERMES collaboration pooled patient-level data from these 5 trials and found that the number needed to treat to reduce disability by at least 1 point on the modified Rankin scale was 2.6. 1 The American Heart Association/American Stroke Association updated guidelines to incorporate MT as a Class I recommendation for LVO strokes presenting within 6 hours from the last known well time. 2 In 2018, the results of DAWN and DEFUSE-3 studies showed the benefit of MT beyond the traditional 6-hour window for patients selected based on imaging criteria (diffusion-weighted imaging [DWI]–clinical mismatch in DAWN and core–perfusion mismatch in DEFUSE-3). 3, 4 Most of these trials excluded patients with a large core (>70 mL on CT perfusion or DWI or Alberta Stroke Program Early CT Score <6) because of the high probability of poor outcomes with less viable brain tissue. However, it remains unclear if the only imaging findings that matter when selecting these patients are the volume of infarcted and penumbral tissue.